Air traffic management innovation and UK business opportunity - Brooker, Peter (Cranfield University, 2008)
ATM (Air Traffic Management) and the associated UK business opportunities are huge topics, so the presentation sketches key issues. It includes lessons from the past, some ideas about the future, and case studies. The ATM system is big and complicated, so innovation has to combat system inertia. Two complementary ‘New ATM paradigms’, SESAR and NextGen, aim to break out of the limits inherent in the current ATM system. To innovate successfully in ATM, be part of the planned future that actually gets developed, and/or create/fill a need that is not yet in the plans.